2022
DOI: 10.1039/d1fo03219d
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderic acid A from Ganoderma lucidum protects against alcoholic liver injury through ameliorating the lipid metabolism and modulating the intestinal microbial composition

Abstract: Alcoholic liver injury is mainly caused by long-term excessive alcohol consumption and has become a global public threat to human health. It is well known that Ganoderma lucidum has excellent beneficial...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 81 publications
(102 reference statements)
1
13
0
Order By: Relevance
“…38 Serum TC, TG, LDL-C and HDL-C levels are closely related to the occurrence of glucose and lipid metabolic disorders. 39 Our study showed that alloxan injection caused significant lipid metabolic abnormalities by increasing the TC, TG and LDL-C levels, while decreasing the HDL-C levels. However, p-synephrine administration might alleviate these conditions.…”
Section: Papermentioning
confidence: 55%
“…38 Serum TC, TG, LDL-C and HDL-C levels are closely related to the occurrence of glucose and lipid metabolic disorders. 39 Our study showed that alloxan injection caused significant lipid metabolic abnormalities by increasing the TC, TG and LDL-C levels, while decreasing the HDL-C levels. However, p-synephrine administration might alleviate these conditions.…”
Section: Papermentioning
confidence: 55%
“…In addition, Prevotellaceae_NK3B31_group, uncultured_bacterium_f_Prevotellaceae, which are from Prevotellaceae also enriched in the BI group. The higher abundance of Prevotellaceae not only protects intestinal epithelial cells against oxidative stress, thereby, alleviating inflammatory symptoms in patients with inflammatory bowel diseases, but also beneficial for preventing obesity ( 103 , 104 ). Consistent with this study, Jerusalem artichoke inulin also enriched several genera of the Prevotelaceae family, and improved lipid metabolism in type 2 diabetes mice ( 105 ).…”
Section: Discussionmentioning
confidence: 99%
“…LPS intraperitoneal injection accelerates the production of ROS from inflammatory cells, which further aggravates ALI and leads to chronic inflammation. Whereas CAT serves as one of the primary ROS scavengers, and thus activation of CAT accelerates the elimination of ROS [ 24 ]. Our results display that the blockade of LPS-induced oxidative stress is associated with the amelioration of ALI.…”
Section: Discussionmentioning
confidence: 99%